DETERMINATION OF THE RISK AT WORKPLACE, ASSESSMENT AND ITS RANK CALCULATION, IN MINING ACTIVITIES - ZEQIRI, Kemajl; KORTNIK, Joze; MIJALKOVSKI, Stojance (GeoScience Engineering, 2020)
Compared to the major industries, mining industry has a high risk accident potential. Over ten thousand miners are killed every year, and this is just the official figure. It is assumed that the number of the injured might exceed one hundred thousand miners, and many of them remain disable [1,2]. The history of mining is linked to the development of society itself, while the regulations on mine safety can be traced back to the Roman times. Significant mining accidents and disasters were reported since the beginning of the year 1800 [2,3]. Several pathways to mine accidents have been identified within the 200-year experience, where the agents have been: hit, inrush, outbursts, explosion, falling, sliding, lifting, poisoning, etc., in different work places, such as stope-work, transport, drift-discharge, transport, maintenance, etc. Despite having identified the causality (agent) long time ago, the number of mining accidents are still disturbing. This paper aims to assess the risk from particular agents at a workplace, trending this way to determine the risk rank through empirical formulas, through parameter “P” as an accident occurrence parameter and relevant statistics on mining accidents. Keywords: Agent; Assessment; Mine; Risk; Safety DOI 10.35180/gse-2020-0032